The biblical roots of Mormonism: [over 1000 scriptures referenced from the Bible] - Shuster, Eric (CFI, 2010)
Premortal life -- Satan -- Adam and Eve -- God the Father -- Jesus Christ -- The Holy Ghost -- The Godhead -- Mary -- Scripture -- Apostasy and restoration -- The priesthood -- Revelation and prophets -- Joseph Smith -- Church organization -- Church practices -- Missionary work -- Ordinances and covenants